International cooperation of hospital ship SS HOPE in Natal (1972): health care and education - Djailson José Delgado Carlos; Maria Itayra Padilha; Maria Lígia dos Reis Bellaguarda; Jaime Alonso Caravaca-Morera
ABSTRACT Objective: to analyze the activities developed by hospital ship SS HOPE in Natal. Method: this is a qualitative, socio-historical study, elaborated from documentary sources and 16 interviews with health professionals. Thematic Oral History was used for data treatment and analysis. Results: the empirical material identified a wide schedule of courses and lectures as well as made it possible to elaborate the following categories: Health education on hospital ship SS HOPE; Legacy of international cooperation of hospital ship SS HOPE; Statements about the season of hospital ship SS HOPE. Final considerations: the arrival and stay of this hospital ship, for ten months, is the result of negotiations between the University, the State Government and the People to People Foundation. During their stay, education and health care actions were carried out, with the joint participation of health professionals, Potiguares and Americans.